Mimicking prophage induction in the body: induction in the lab with pH gradients - Miller-Ensminger, Taylor; Garretto, Andrea; Stark, Nicole; Putonti, Catherine (PeerJ, 2020)
The majority of bacteria within the human body are lysogens, often harboring multiple bacteriophage sequences (prophages) within their genomes. While several different types of environmental stresses can trigger or induce prophages to enter into the lytic cycle, they have yet to be fully explored and understood in the human microbiota. In the laboratory, the most common induction method is the DNA damaging chemical Mitomycin C. Although pH has been listed in the literature as an induction method, it is not widely used. Here, we detail a protocol for prophage induction by culture under different pH conditions. We explored the effects of pH on prophage induction in bacterial isolates from the bladder, where the pH is well documented to vary significantly between individuals as well as between healthy individuals and individuals with urinary tract symptoms or disease. Using this protocol, we successfully induced phages from seven bladder E. coli strains. Testing conditions and stressors appropriate to the environment from which a lysogen is isolated may provide insight into community dynamics of the human microbiota.
Keywords: Induction; Bacteriophage; Lysogens; pH